2010
DOI: 10.2298/avb1006585k
|View full text |Cite
|
Sign up to set email alerts
|

Testing the effect of different electrotherapeutic procedures in the treatment of canine ankylosing spondylitis

Abstract: This paper presents the results of studies on the effects of suppression of chronic pain by currents with low (TENS), medium (Intf) and high (MT) frequencies, in dogs with ankylosing spondilytis. Prior to imaging diagnostics the dogs were clinically observed, trias was estimated, as well as habitus, neurological signs and degree of pain. After a 10 day treatment it was clear that all three treatments resulted in a significant decrease of pain at rest, during activity or during palpation. TENS currents ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…In our study laser therapy was added to the physiotherapy treatment protocol in 6 of the 10 cases from the G1, in order to obtain fast reduction of clinical symptoms such as lameness and pain, subjectively assessed by HCPI questionnaire and clinical exam- Krstic et al (2010) obtained a significant pain reduction after using TENS in dogs with ankylosing spondylitis. Pain reduction was observed through VAS (Visual Analogue Scale) (Krstic et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In our study laser therapy was added to the physiotherapy treatment protocol in 6 of the 10 cases from the G1, in order to obtain fast reduction of clinical symptoms such as lameness and pain, subjectively assessed by HCPI questionnaire and clinical exam- Krstic et al (2010) obtained a significant pain reduction after using TENS in dogs with ankylosing spondylitis. Pain reduction was observed through VAS (Visual Analogue Scale) (Krstic et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Due to several confounding factors in both of studies, they had a moderate-to-high risk of bias. The Krstic et al [33] study on ankylotic spondylosis in dogs also showed a high risk of bias and reported positive effects from TENS treatment in some pain-related outcome variables compared with other treatments. In the Sharifi et al [5] study, an objective mechanical measure of tendon tensile strength was used, revealing the difference between the TENS-treated group in relation to the control group, albeit the TENS-treated tendon was not equivalent to the normal tendon at the time of the final examination.…”
Section: Clinical Effectsmentioning
confidence: 99%
“…Five studies, three in dogs [32][33][34] and two in horses [5,35], were included in the review (Table 4).…”
Section: Transcutaneous Electrical Nerve Stimulationmentioning
confidence: 99%
See 2 more Smart Citations